2016
DOI: 10.1007/s11764-016-0581-0
|View full text |Cite
|
Sign up to set email alerts
|

Do cancer survivors develop healthier lifestyle behaviors than the cancer-free population in the PLCO study?

Abstract: Background Current studies report mixed results in health status and health behaviors after a diagnosis of cancer. The aim of our study is to investigate potential differences in lifestyle factors among cancer survivors and cancer-free individuals in a prospective cohort study conducted in the United States. Methods Using data from the Prostate, Lung, Colorectal and Ovarian (PLCO) Trial, 10,133 cancer survivors were identified and compared to 81,992 participants without cancer to evaluate differences in body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 58 publications
(51 reference statements)
4
12
0
Order By: Relevance
“…Whilst evidence is limited and inconsistent, there are a number of studies suggesting that cancer survivors make positive changes to health behaviours after a cancer diagnosis [9,10,11,12], and cancer survivors have healthier lifestyle behaviours than those who are cancer-free [13,14,15]. These findings emanate the notion that the period after a cancer diagnosis be considered as a “teachable moment”, whereby cancer survivors may be receptive to lifestyle change messages and may be more motivated to make healthy behaviour changes [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst evidence is limited and inconsistent, there are a number of studies suggesting that cancer survivors make positive changes to health behaviours after a cancer diagnosis [9,10,11,12], and cancer survivors have healthier lifestyle behaviours than those who are cancer-free [13,14,15]. These findings emanate the notion that the period after a cancer diagnosis be considered as a “teachable moment”, whereby cancer survivors may be receptive to lifestyle change messages and may be more motivated to make healthy behaviour changes [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Differences may exist in health behaviours by duration of cancer survivorship (long-term versus recent survivors). In a U.S. prospective cohort study, the Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial revealed that recent cancer survivors were more likely to engage in moderate and strenuous physical activity when compared to long-term survivors, but there was no difference for BMI or smoking status [13]. This might suggest changes in health behaviour are not stable across the cancer continuum.…”
Section: Introductionmentioning
confidence: 99%
“…A quarter to a third of the UK population meet the PA guidelines and this declines with age; 21% of men and 18% of women aged 65-74 years achieve the recommendations, dropping to 9% and 6% respectively in the over 75s [31]. There are no similar comprehensive data available yet for cancer survivors, but there is some evidence suggesting an increased rate of sedentary behaviour and reduction in PA levels post-diagnosis [8,32,33]. Adherence to recommended levels is lower in older survivors [34].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, few cancer patients actually comply with these recommendations [7]. PA levels are reported to drop after a cancer diagnosis [8] and influencing factors include: older age, previous comorbidities, cancer stage, and treatment side-effects [9][10][11][12][13]. Lack of confidence or knowledge regarding appropriate exercise levels, and limited access to targeted programmes and/or facilities where patients can exercise with others in the same situation are also common barriers [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a cancer diagnosis is often viewed as a “teachable moment” when patients may be considering changing current lifestyle habits, such as smoking cessation and maintenance of a healthy weight through diet (Hawkins et al., 2017). There is growing evidence of the importance of diet and nutrition in cancer survivorship.…”
Section: Introductionmentioning
confidence: 99%